Bichromatic method for identification of clear-sky scenarios over ground pixel viewed from space - Sanghavi, Suniti Vinod; Platt, Ulrich; Landgraf, Jochen (Applied optics, 2010)
We propose a method for identifying clear-sky scenarios from a measurement time series over satellite-observed ground pixels of unknown surface albedo and aerosol type. The lack of a general monotonic relationship between aerosol loading and observed reflectance encumbers the ordering of the observation time series according to aerosol loading. This problem is ameliorated by using two wavelengths at which the surface albedos are known to differ. Treating an observation as being cloud/aerosol free allows for the determination of the corresponding Lambertian equivalent albedo, the relative contrast of which at the two wavelengths varies monotonically with respect to aerosol-loading, clear-sky and completely clouded scenarios representing the extreme cases. Applying this method to the Scanning Imaging Absorption Spectrometer for Atmospheric Chartography measurements over a nondark surface, we validate it by comparing measured against modeled O2A- and B-band absorption at the retrieved albedo in an aerosol-free atmosphere.
Gesehen am 07.08.2023
Elektronische Reproduktion der Druckausgabe